Bhutan Urban Policy Notes : Urban Resilience - World Bank (World Bank, Washington, DC, 2019)
This paper is part of a series of four Urban Policy Notes that identify emergent challenges to Bhutan’s increasing urbanization and its ramifications for growth, livability, and sustainability in line with the directives of the Twelfth Five-Year Plan (FYP) for 2018-23 and the Vision 2020. The four notes are: (i) Regional Development, (ii) Municipal Governance and Finance, (iii) Affordable Housing, and (iv) Urban Resilience. These notes build on the long engagement between the Royal Government of Bhutan (RGoB) and the World Bank on urban issues as well as the operations under the Bhutan Urban Development Project First (1999-2006) and Second (2010-19). This note specifically draws from the ongoing support to build a safe, sustainable, and climate-resilient Bhutan through the Hydromet Services and Disaster Resilience Regional Project, preparation of Bhutan’s Strategic Program for Climate Resilience Project, Improving Seismic Resilience Project, and related technical assistance. It is intended to support the RGoB on key and emerging topics relevant in the context of increasing urbanization and vulnerability to weather, water, and climate hazards, and to guide the Bank’s future analytical and investment support on urban- and resilience-related challenges.